Scenarios for the hydrogen market and strategic options for MNEs - Bartjan Pennink; Duën Holterman (The Central European Review of Economics and Management (CEREM), 2024)
Aim: The purpose of this article is to investigate how hydrogen-based energy will be implemented in the future economy and to find strategic options in the future hydrogen market for multinational enterprises (MNEs) active in the energy sector. Design/Research methods: The current literature on hydrogen production tends to focus on the technical and cost aspects, while there is limited attention on how one could implement hydrogen in the future. In this explorative research, interviews with experts formed a basis and the scenario planning methodology was used. Conclusions/findings: The three scenarios that were developed are based on the potential strategies of the European Union, which are Hydrogen Independence, Cost Optimization, and Energy Security. Based on a literature review, five key characteristics that will impact the functioning of the future hydrogen economy were selected. By using notions from the environmental- and positioning schools of Mintzberg, strategic options for MNEs were identified in each scenario. In all three scenarios, the implementation of hydrogen-based alternatives will differ. Besides this, the strategic options that MNEs can obtain will also change. Originality; value of the article: This article helps us understand how hydrogen-based energy sources will be implemented into the economy, taking on board the priorities of the European Union. Furthermore, it gives managers of MNEs guidance to identify strategic options that fit alongside their firms' strategy. Finally, this research gives an incentive for future research as, on several topics, the interviewees could not find consensus.
Keywords: L22; L25; Q40; Q47; 330; Hydrogen Market; Multinational Enterprises (MNEs).; Renewable Energy Sources (RES); Scenario Planning; Strategy